Concurrent validity and reliability of two portable powermeters (Power2Max vs. PowerTap) to measure different types of efforts in cycling - Iglesias-Pino, J.; Herrero-Molleda, A.; Saavedra-García, M. Á.; García-López, J. (Sensors, 2023)
The purpose was to assess the concurrent validity and reliability of two portable powermeters (PowerTap vs. Power2Max) in different types of cycling efforts. Ten cyclists performed two submaximal, one incremental maximal and two supramaximal sprint tests on an ergometer, while pedaling power and cadence were registered by both powermeters and a cadence sensor (GarminGSC10). During the submaximal and incremental maximal tests, significant correlations were found for power and cadence data (r = 0.992-0.997 and 0.996-0.998, respectively, p < 0.001), with a slight power underestimation by PowerTap (0.7-1.8%, p < 0.01) and a high reliability of both powermeters (p < 0.001) for measurement of power (ICC = 0.926 and 0.936, respectively) and cadence (ICC = 0.969 and 0.970, respectively). However, during the supramaximal sprint test, their agreement to measure power and cadence was weak (r = 0.850 and -0.253, p < 0.05) due to the low reliability of the cadence measurements (ICC between 0.496 and 0.736, and 0.574 and 0.664, respectively; p < 0.05) in contrast to the high reliability of the cadence sensor (ICC = 0.987-0.994). In conclusion, both powermeters are valid and reliable for measuring power and cadence during continuous cycling efforts (~100-450 W), but questionable during sprint efforts (>500 W), where they are affected by the gear ratio used (PowerTap) and by their low accuracy in cadence recording (PowerTap and Power2Max).